2011
DOI: 10.1021/ie2000709
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a Solid Amine Sorbent for CO2 Capture by Pressure Swing Adsorption

Abstract: This study showed that a solid amine, composed of poly(ethylenimine) immobilized into a CARiACT G10 silica substrate, is a feasible sorbent for applications in a pressure swing adsorption (PSA) process for postcombustion CO2 capture. This deduction materialized from an extensive study of the behavior of this material over a wide range of industrially relevant conditions using thermogravimetric analysis. The temperature ranged from 40 to 100 °C, the CO2 partial pressure ranged from 1.2 to 100 vol % with the tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(107 citation statements)
references
References 47 publications
5
101
1
Order By: Relevance
“…The formed secondary amines exhibited a larger increase in cyclic CO 2 adsorption capacities than the primary amines. The supports including PMMA, polystyrene (PS) and silicon dioxide were also performed by the DOE/NTEL's group (Gray et al, 2009;Ebner et al, 2011;Jiang et al, 2011;. The nano-layered amine-based adsorbents using layer-by-layer nanoassembly technology via alternate deposition of PEI and an oppositely-charged polymer like PMMA and polystyrene sulfonate prepared by NTEL people were also used for CO 2 capture.…”
Section: Fig 3 (Continued)mentioning
confidence: 99%
“…The formed secondary amines exhibited a larger increase in cyclic CO 2 adsorption capacities than the primary amines. The supports including PMMA, polystyrene (PS) and silicon dioxide were also performed by the DOE/NTEL's group (Gray et al, 2009;Ebner et al, 2011;Jiang et al, 2011;. The nano-layered amine-based adsorbents using layer-by-layer nanoassembly technology via alternate deposition of PEI and an oppositely-charged polymer like PMMA and polystyrene sulfonate prepared by NTEL people were also used for CO 2 capture.…”
Section: Fig 3 (Continued)mentioning
confidence: 99%
“…Ritter et al also showed that porous silica (CARiACT G10 from Fuji Silysia) supported PEI423 sorbent had essentially no capacity loss after 78 concentration sweep cycles at 80 C. 45 In fact, it has recently been demonstrated that the sorbent degradation under dry CO 2 conditions depends on many factors, such as the nature of amines, the stripping gas and the desorption temperature.…”
Section: 48-51mentioning
confidence: 99%
“…CO 2 removal by adsorption process is promising in terms of relatively high energy efficiency and is being investigated extensively in the community with several variations in the operating configurations such as vacuum, pressure or temperature swing, and also with varied sorbents (Choi et al, 2009;Chou and Chen, 2004;Ebner et al, 2011). One of the configurations is to perform rapid thermal swing (RTSA) (Lively et al, 2009) of CO 2 using amine sorbents supported in a hollow fiber configuration, which has been studied both experimentally and through models Rezeai et al, 2014;Kalyanaraman et al, 2014).…”
Section: Application: Co 2 Sorption In Hollow Fiber Based Sorbentmentioning
confidence: 99%